Dendrimers for gene delivery – a potential approach for ocular therapy?. (19th July 2013) - Chaplot, Sahil P.; Rupenthal, Ilva D.
Abstract Objectives A vast number of blinding diseases have genetic aetiologies and may be treated by molecular based therapies such as antisense oligonucleotides or short interfering RNA. However, treatment success of ocular gene therapy is highly dependent on efficient delivery of such molecules. Key findings The majority of clinical studies for ocular gene therapy utilize viral vectors. While these have proven highly efficient, they show limited loading capacity and pose significant safety risks owing to their oncogenic and immunogenic effects. Non‐viral gene carriers have emerged as a promising alternative with dendrimers providing great potential for gene therapy because of their size, shape and high density of modifiable surface groups. However, while dendrimers have been used extensively for drug and gene delivery to other organs, only a few studies have been reported on the eye. Summary This review focuses on the development of dendrimers for gene delivery with special emphasis on ocular gene therapy. Different synthesis approaches and types of dendrimers are discussed. Ocular gene therapy targets are highlighted with an overview of current clinical studies. The use of dendrimers in ocular gene delivery in comparison to liposomes and nanoparticles is also discussed. Finally, future prospects of tailored multifunctional dendrimers for ocular gene therapy are highlighted.